Uji Daya Anthelmintik Ekstrak Etanol Biji Pepaya (Carica papaya) Terhadap Cacing Ascaris suum Secara In Vitro - Olivia Maria Ujan; Agus Saputra; Aji WINARSO (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2021)
The purpose of this study was to determine the anthelmintic test of ethanol extract of papaya seeds on Ascaris suum worms in vitro and to find out the compounds contained therein based on phytochemical tests. The materials used were papaya seeds (Carica papaya), Ascaris suum worms, 70% ethanol, 0,9% NaCl, and Pyrantel pamoate. Extraction of papaya seeds was done by maceration method using 70% ethanol solvent. Identification of Ascaris suum worms was carried out based on the morphological characteristics of the worm (female/male, length, and diameter). Testing of ethanol extract of papaya seeds was carried out in 4 groups consisting of three treatment groups and one control group. Three treatment groups used ethanol extract of papaya seeds with a concentration of 2,5%, 5%, 7,5%, and the control group using pyrantel pamoate 7,5%. Potential of ethanol extract of papaya seeds was seen from the time needed to kill Ascaris suum worms. Where the ethanol extract of papaya seeds was 2,5% with an average mortality time of 5,96 hours, a concentration of 5% with a mean of 3,98 hours, a concentration of 7,5% with a mean of 2,52 hours and a control group with a mean time of death of 2,18 hours. The results showed that there was a statistically significant effect (P<0,05) on P1 and P2 and there was no significant effect (P>0,05) on P3. It can be concluded that immersion using pyrantel 7,5% is still higher than P1 and P2 and immersion using pyrantel 7,5% has the same anthelmintic effect as P3. In the phytochemical test, ethanol extract of positive papaya seeds contained saponin, tannin, alkaloid, phenol, flavonoid and triterpenoid.